2011
DOI: 10.1111/j.1346-8138.2011.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heparanase and matrix metalloproteinase‐9 in patients with cutaneous malignant melanoma

Abstract: Elevated heparanase and matrix metalloproteinase (MMP)-9, frequently found in human cancer, is a major cause of degradation of the extracellular matrix (ECM) and basement membrane (BM), thus facilitating tumor cell migration and invasion. Although a lot of work has been done, the role of heparanase and MMP-9 has not been delineated in skin cancer progression. The purpose of this study was to do such an exploration. To investigate the role of heparanase and MMP-9 in cutaneous malignant melanoma (CMM) developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
(91 reference statements)
5
20
0
1
Order By: Relevance
“…Monoclonal antibodies against MMP-2 and MMP-9 were also included in this experiment because both have a role in melanoma development [27], [28].…”
Section: Resultsmentioning
confidence: 99%
“…Monoclonal antibodies against MMP-2 and MMP-9 were also included in this experiment because both have a role in melanoma development [27], [28].…”
Section: Resultsmentioning
confidence: 99%
“…To study the effects of new antitumoral agents, many biomarkers have been investigated including matrix metalloproteinases (MMPs) which are regulated by their tissue inhibitors (TIMP). Chen and colleagues [56] analyzed samples from patients and reported that there is a differential expression of MMP-9, which is present in early stage of benign lesions and a significant increase occurs in advanced malignant melanoma stages. This variation in MMP-9 activity might contribute to degradation of extracellular matrix, thereby promoting carcinogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has shown marked increase in MMP-9 and Heparanase in cutaneous melanoma cells, especially ones that have metastasized to regional lymph nodes, as compared to tumors with negative SLN [24]. In another study, it has been clearly shown that MDA-9/Syntenin has a critical role with regard to melanoma metastasis.…”
Section: Progression From the Primary Site To The Metastatic Deposit:mentioning
confidence: 99%